Cultivation of green algae Chlorella vulgaris & Cosmarium pyramidatum in secondary treated wastewater and determination of protein biomass productivity - جـورج ديـب,; علي بكداش , (Latakia University Journal -Biological Sciences Series, 2022)
In this research, green algae Chlorella vulgaris & Cosmarium pyramidatum were isolated from the fountain basin of Tishreen University and cultured under the appropriate cultivation conditions of temperature and illumination (temperature 25 ± 2 °C, illumination intensity 2500 lux, light cycle 16 light/8 dark) on 3N-BBM culture medium. +V, liquid and solid. The isolated green algae were also cultured in secondary treated sewage water from Al-Ruwaimia plant under the appropriate cultivation conditions of temperature and lighting. During the algal growth period, pH, electrical conductivity (EC) and dissolved oxygen were measured every 3 days for 24 days. The growth of the isolated green algae was accompanied by an increase in the values ​​of pH and dissolved oxygen and a decrease in electrical conductivity, and the green algae Chlorella vulgaris was more adapted to growth, as it recorded the highest growth rate of 3.2 cells/hour and the lowest doubling time of 1.34 hours in the secondary treated wastewater, and obtaining a biomass that reached The percentage of protein in it to 47.1%.